DETECTION OF HETEROZYGOUS BETA THALASSAEMIA IN THE SIBLINGS OF KNOWN BETA THALASSAEMIA MAJOR CHILDREN - Khattak, Imran ud din; Shah, Mukammil; Khattak, Sania Tanweer; Zaidi, Alia Nahid; Raziq, Fazli (Journal of Postgraduate Medical Institute, 2011)
Objective: To detect heterozygous Beta Thalassaemia trait in the siblings (brothers and sisters) of known beta Thalassaemia major children by haemoglobin electrophoresis.